Anthropometric Indices of Giardia-Infected Under-Five Children Presenting with Moderate-to-Severe Diarrhea and Their Healthy Community Controls: Data from the Global Enteric Multicenter Study - Shamsun Nahar Shaima; Sumon Kumar Das; Shahnawaz Ahmed; Yasmin Jahan; Soroar Hossain Khan; Gazi Md. Salahuddin Mamun; Abu Sadat Mohammad Sayeem Bin Shahid; Irin Parvin; Tahmeed Ahmed; A. S. G. Faruque; Mohammod Jobayer Chisti (MDPI AG, 2021)
Among all intestinal parasitosis, giardiasis has been reported to be associated with delayed growth in malnourished children under 5 living in low- and middle-income countries. Relevant data on the nutritional status of children aged 0-59 months presenting with moderate-to-severe diarrhea (MSD) and giardia infection were collected from sentinel health facilities of the Global Enteric Multicenter Study's (GEMS) seven field settings, placed in diverse countries of Sub-Saharan Africa and South Asia between, December 2007 and February 2011. Then, this study analyzed a robust dataset of study participants (n = 22,569). Children having giardiasis with MSD constituted as cases (n = 1786), and those without MSD constituted as controls (n = 3470). Among the seven field sites, symptomatic giardiasis was 15% and 22% in Asian and African sites, respectively, whereas asymptomatic giardia infection (healthy without MSD) in Asian and African sites was 21.7% and 30.7%, respectively. Wasting and underweight were more frequently associated and stunting less often associated with symptomatic giardiasis (for all, p < 0.001). Symptomatic giardiasis had a significant association with worsening of nutritional status in under-five children. Improved socio-economic profile along with proper sanitation and hygienic practices are imperative to enhance child nutritional status, particularly in resource limited settings.